Los inicios de la prosa castellana en el Perú - Coello, Óscar (2018)
This paper studies the two most important texts with which Spanish prose begins in Peru: Códex vindobunensis and Anónimo sevillano. At a time when history was a literary genre, this paper examines the moments of fiction, as well as the rhetorical resources present in those first two artistic discourses. Complementarily, it highlights the case of the foundation of Piura specified by the Anónimo.